Implementation of Sort Card Method to Improve Motivation and Learning Outcomes of MAN Batu Students - Rasmuin Rasmuin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
This classroom action research uses the Kemmis and Mc Taggart model to determine the effect of the sort card method in learning History of Islamic Culture. The subjects of this study were 34 students of grade XI IPS 2 MAN Batu, East Java. The instruments in this study include observation, documentation, interviews and tests. The collected data were analyzed using descriptive analysis techniques. The results showed that the sort card method was able to increase student learning motivation. It is evident from the increasing active participation in the learning process. This method is also able to improve student learning outcomes. It is evident from the increasing of learning outcomes in cycle 1 and 2. At the time of the pre-cycle, the highest score obtained by students was 80 with a passing percentage of 23%. This score increased in first cycle with the highest score of 90 with a percentage of completeness of 71%. In the second cycle student learning outcomes have increased again. The highest score was recorded at 98 with the percentage of completeness increased to 88%